Structural transformation of Bi1−x/3V1−xMoxO4 solid solutions for light-driven water oxidation. Issue 9 (1st February 2016) - Terebilenko, Kateryna V.; Bychkov, Konstantin L.; Baumer, Vyacheslav N.; Slobodyanik, Nikolay S.; Pavliuk, Mariia V.; Thapper, Anders; Tokmenko, Inna I.; Nasieka, Iurii M.; Strelchuk, Viktor V.
Abstract : The influence of Mo content in the solid solutions of Bi1− x /3 V1− x Mo x O4 ( x = 0.05–0.20) on the morphology, band gap, structure and light-driven water oxidation properties has been studied by SEM, powder XRD and vibrational spectroscopy. Abstract : The influence of molybdenum content in the solid solutions of Bi1− x /3 V1− x Mo x O4 ( x = 0.05–0.20) on the morphology, band gap, structure and light-driven water oxidation properties has been studied by scanning electron microscopy, X-ray powder diffraction and vibrational spectroscopy (Raman and infrared). To find out the peculiarities of structural changes for bismuth scheelite-related oxides containing both vanadium and molybdenum crystals of Bi0.98 V0.93 Mo0.07 O4 have been grown from a K–Bi–V–Mo–O high-temperature melt and characterized by single crystal X-ray diffraction. For the scheelite-related framework both V and Mo were found to occupy the same positions lowering the point group symmetry of tetrahedra from 4/ m to 2/ m giving monoclinic distortion for solid solutions with x = 0.05–0.10. The most promising photocatalytic performance was obtained for Bi0.96 Mo0.10 V0.90 O4, in which the oxygen evolution could reach 21 μM in 50 s under visible light of LEDs, λ = 470 ± 10 nm, and 820 μE cm −2 s −1 . The changes in catalytic properties are shown to be governed by a crystal structure strain with a maximum obtained for the boundary sample between the monoclinic and tetragonal phase.